Differential biochemical response of rat kidney towards low and high doses of NiCl2 as revealed by NMR spectroscopy. Issue 2 (16th September 2011) - Tyagi, Ritu; Rana, Poonam; Gupta, Mamta; Khan, Ahmad Raza; Bhatnagar, Deepak; Bhalla, P. J. S.; Chaturvedi, Shubhra; Tripathi, Rajendra P; Khushu, Subash
ABSTRACT Heavy metals are known for their associated nephrotoxicity and nickel is no exception. An integrated metabonomic approach, based on high‐resolution 1H NMR spectroscopy, was applied to determine the acute biochemical effects of NiCl2 on the renal tissues of rats. Kidney homogenates from rats treated with NiCl2 at two dose levels (4 and 20 mg kg−1 b.w., i.p.) and those from controls were analysed using 1H NMR spectroscopy and also assessed for antioxidant parameters at days 1, 3 and 5 post‐dose. The major metabolite changes corresponding to nickel exposure were related to amino acids, osmolytes and energy metabolites. Differential responses were observed in 1H NMR spectra with exposure to low and high doses of NiCl2. For high doses, 1H NMR spectral analysis revealed alterations in renal tissues, along with damage to the cortical and papillary region and depletion of renal osmolytes such as betaine, trimethyl amine oxide, myo‐inositol and taurine, which persisted until day 5 post‐dose. The metabolite profile of 1H NMR spectra obtained from animals treated with lower dose of NiCl2 initially increased as an immediate stress response and then showed signs of recovery with the passage of time. NMR spectral analysis was well corroborated with histopathological and oxidative stress results. Nickel‐induced oxidative stress was observed in both groups of animals with increased levels of antioxidant parameters at initial time points, but continued to increase in the high‐dose group. The present study shows a huge potential of metabonomics for mapping organ‐based metabolic response during heavy metal toxicity. Copyright © 2011 John Wiley & Sons, Ltd.